(untitled) (International Journal of Islamic Business, 2016)
Business incubators have been proven as effective in creating jobs and accelerating the growth of new businesses. The purpose of this paper is to investigate and identify the situation and factors of business incubator as a catalyst to facilitate successful implementation such as, 1) young entrepreneur, 2) job creation, and 3) Networking business incubators and (SMEs) among OIC countries. Although the basic concept of business incubation remains until today, there have been several enhancements to the capability of business incubators to create entrepreneurs and improve economic driver. Moreover, institutional theory stated that business incubators have generated some positive results for small businesses’ success. The nature of this research is mainly a mixed methods approach such as case study and qualitative (literature review). Case studies reflect a comparative analysis of entrepreneurship ecosystem between Asia and Arab world. Some data retrieved from journals, articles, and business incubator report. Findings of this paper show that the rapid expansion of business incubators in Asia and the Arab world is an important phenomenon affecting the economic growth in those countries. Moreover, much attention and great support from central and/or local government has relation on growth in incubation industry. Furthermore, partnerships and sharing among different incubators is a crucial component to make incubators more successful. The findings of this paper help governments and local authorities to shape future polices for incubation industry, entrepreneurs, and economics development among OIC.